The complete chloroplast genome sequence of Camellia sinensis cultivar ‘Qiancha1’ from Guizhou Province, China - Chun Yang; Dahe Qiao; Yan Guo; Juan Chen; Zhengwu Chen (Mitochondrial DNA. Part B. Resources, 2022)
The complete chloroplast genome sequence of Camellia sinensis cultivar ‘Qiancha 1’ (QC1), an excellent tea plant cultivar was determined in this study. The cp genome of QC1 is 157,024 bp in length and includes a large single copy (LSC, 86,585 bp), a small single copy (SSC, 18,277 bp) and a pair of inverted repeats (IRa and IRb, 26,081 bp). The overall GC content is 37.3%. A total of 137 genes were annotated, including 92 protein coding, 37 tRNA, and eight rRNA genes. Phylogenetic analysis showed that QC1 has the closest evolutionary relationship with C. sinensis cultivar ‘Anhua’ from Hunan, China. The complete cp genome of QC1 provides a resource for further research on the phylogeny and taxonomy of Sect. Thea (L.) Dyer.